Rayleigh waves speed in transversely isotropic material - Rehman, A.; Khan, A.; Ali, A. (Engineering Transactions, 2006)
Rayleigh wave speed in transversely isotropic material is studied. A very simple technique is adopted to solve the secular equation. Speed in some transversely isotropic materials is calculated.